A Case of Accidental Vincristine Overdose and Effective use of Therapeutic Plasma Exchange in Its Management - Goyal, Hari; Khetarpal, Anil; Jain, Amit (Indian Journal of Medical and Paediatric Oncology, 2020)
Vincristine is a common drug used in hematological malignancy with a maximum per dose limited to 2 mg mainly to limit neurotoxicity. Vincristine overdose and wrong route of administration, though has been reported in world literature, but its appropriate management is still undefined. We report a case of Hodgkin lymphoma being treated with adriamycin, bleomycin, vinblastine and dacarbazine protocol, where vincristine was accidently administrated instead of vinblastine due to its “look-alike, sound-alike” nature. The patient developed severe toxicity due to the same, which was effectively managed by therapeutic plasma exchange.
Keywords: Look-alike; sound-alike drugs; medication error; overdose; therapeutic plasma exchange; vincristine